Community health workers can improve male involvement in maternal health: evidence from rural Tanzania - Furaha August; Andrea B. Pembe; Rose Mpembeni; Pia Axemo; Elisabeth Darj (Taylor & Francis Group, 2016)
Background: Male involvement in maternal health is recommended as one of the interventions to improve maternal and newborn health. There have been challenges in realising this action, partly due to the position of men in society and partly due to health system challenges in accommodating men. The aim of this study was therefore to evaluate the effect of Home Based Life Saving Skills training by community health workers on improving male involvement in maternal health in terms of knowledge of danger signs, joint decision-making, birth preparedness, and escorting wives to antenatal and delivery care in a rural community in Tanzania. Design: A community-based intervention consisting of educating the community in Home Based Life Saving Skills by community health workers was implemented using one district as the intervention district and another as comparison district. A pre-/post-intervention using quasi-experimental design was used to evaluate the effect of Home Based Life Saving Skills training on male involvement and place of delivery for their partners. The effect of the intervention was determined using difference in differences analysis between the intervention and comparison data at baseline and end line. Results: The results show there was improvement in male involvement (39.2% vs. 80.9%) with a net intervention effect of 41.1% (confidence interval [CI]: 28.5-53.8; p <0.0001). There was improvement in the knowledge of danger signs during pregnancy, childbirth, and postpartum periods. The proportion of men accompanying their wives to antenatal and delivery also improved. Shared decision-making for place of delivery improved markedly (46.8% vs. 86.7%), showing a net effect of 38.5% (CI: 28.0-49.1; p <0.0001). Although facility delivery for spouses of the participants improved in the intervention district, this did not show statistical significance when compared to the comparison district with a net intervention effect of 12.2% (95% CI: −2.8-27.1: p=0.103). Conclusion: This community-based intervention employing community health workers to educate the community in the Home Based Life Saving Skills programme is both feasible and effective in improving male involvement in maternal healthcare.